1997
DOI: 10.1016/s0029-7844(96)00446-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the bioavailability of oral and intramuscular dexamethasone in women in late pregnancy

Abstract: The bioavailability of 8 mg of oral dexamethasone is similar to that of a 6-mg IM dose, as determined by the area under the curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…( e ) Simulated (lines; 10 × 11 virtual individuals) and observed (data points; from ref. ) mean plasma concentration‐time profiles of dexamethasone after a single oral dose of 8 mg (blue line, filled circles) or a single i.m. dose of 6 mg (solid black line, open circles) in pregnant subjects (mean gestational age: 30 weeks).…”
Section: Resultsmentioning
confidence: 98%
“…( e ) Simulated (lines; 10 × 11 virtual individuals) and observed (data points; from ref. ) mean plasma concentration‐time profiles of dexamethasone after a single oral dose of 8 mg (blue line, filled circles) or a single i.m. dose of 6 mg (solid black line, open circles) in pregnant subjects (mean gestational age: 30 weeks).…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, two reports indicate T max at about 2 hours for oral Dex and 1 hour for i.m. Dex in pregnant women . However, Queckenberg et al .…”
Section: Discussionmentioning
confidence: 96%
“…Dex in pregnant women. 19,20 However, Queckenberg et al 21 reported maximal peak concentrations at 1 hour for oral Dex in fasted adults. Another variable confounding virtually all previous clinical PK studies is that at early times plasma will contain the prodrugs, BetaP or DexP.…”
Section: Discussionmentioning
confidence: 99%
“…It is administered during pregnancy to normalize lung morphology inducing structural and functional maturity in preterm human infants with bronchopulmonary dysplasia and so decreasing mortality [4]. Fetal exposure to an excess of glucocorticoids has been implicated as a causative factor in fetal growth restriction called intrauterine growth retardation (IUGR) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal exposure to an excess of glucocorticoids has been implicated as a causative factor in fetal growth restriction called intrauterine growth retardation (IUGR) [5]. The effects of prenatal Dex therapy on the fetal skeletal system need to be clarified because this kind of therapy can result in more disadvantages than advantages, especially in the long-term consequences in postnatal life and adulthood [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%